Harnessing Predictive Modelling for Education Index : A Dual Approach with Random Forest and Multiple Linear Regression - Olivia Kristianti Kusuma; Jessica; Grace Felicia Christy Widjaya; Helena Margaretha; Ferry Vincenttius Ferdinand; Kie Van Ivanky Saputra (Universitas Pelita Harapan, 2026)
This study explores the predictive modeling of the Education Index (EI) using a dual approach using Random Forest and Multiple Linear Regression (MLR). The data, obtained from